2017
DOI: 10.1371/journal.pone.0177552
|View full text |Cite
|
Sign up to set email alerts
|

Recent tree cover increases in eastern China linked to low, declining human pressure, steep topography, and climatic conditions favoring tree growth

Abstract: Globally, the extent of forest continues to decline, however, some countries have increased their forest extent in recent years. China is one of these countries and has managed to increase their tree cover through huge reforestation and afforestation programs during recent decades as well as land abandonment dynamics. This study investigates tree cover change in the eastern half of China between 2000 and 2010 on three different scales, using random forest modeling of remote sensing data for tree cover in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Li et al (2002) provide evidence that Rhinopithecus was first extirpated from lower elevation during the last 400 years. Higher elevation areas are more remote and difficult for humans to access and utilize and other studies have found less deforestation, more reforestation and afforestation, less range contraction, and less extinction in topographically steep areas (Laliberte and Ripple 2004; Fisher 2011; Sandel and Svenning 2013; Faurby and Svenning 2015; Nüchel and Svenning 2017). Furthermore, many other species in the region, e.g., giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens ), have also been impacted by strong anthropogenic pressure during the recent centuries with population declines and range retractions as consequences (Ceballos and Ehrlich 2002; Zhu et al 2010; Hu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2002) provide evidence that Rhinopithecus was first extirpated from lower elevation during the last 400 years. Higher elevation areas are more remote and difficult for humans to access and utilize and other studies have found less deforestation, more reforestation and afforestation, less range contraction, and less extinction in topographically steep areas (Laliberte and Ripple 2004; Fisher 2011; Sandel and Svenning 2013; Faurby and Svenning 2015; Nüchel and Svenning 2017). Furthermore, many other species in the region, e.g., giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens ), have also been impacted by strong anthropogenic pressure during the recent centuries with population declines and range retractions as consequences (Ceballos and Ehrlich 2002; Zhu et al 2010; Hu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This also means that there is a high probability that many of the regions’ threatened species are refugee species, confined to suboptimal habitat. On the other hand, it should be noted that there are large reforestation and afforestation programs going on in China, especially since end of 1990s (Yin et al 2005; Zhang and Song 2006; Peng et al 2014; Nüchel and Svenning 2017). …”
Section: Introductionmentioning
confidence: 99%
“…During the 2000–2015 period, because of higher human population density and urbanization, forests in hilly areas were usually associated with higher demand for forest natural resources (e.g., food, fibre and fuel) for developed lands and transportation infrastructure compared with forests in mountainous areas. In contrast, many mountainous areas that have experienced a decline in population density and an increase in tree cover (a proxy for productivity) appeared in the areas with marginal farmlands abandoned in recent years, in particular, in mountainous areas with steep slopes, attributable to rural‐to‐urban migration in China (Nüchel et al., 2019; Nüchel & Svenning, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Forest fires are the most widespread and critical disturbance in boreal and temperate forest ecosystems (Ying et al 2018). While China's forest cover has increased by about 10% as a result of sustainable forest management since the late 1970s (Nöchel and Svennin 2017), the forest area ecosystems affected by fire is increasing at the alarming rate of roughly 600 thousand hectares per year (Yang et al 2010). Climatic conditions and forest composition in northeast China, much like those in the United States of America, Canada, Australia, and Mediterranean Europe, are favourable to forest fires.…”
Section: Introductionmentioning
confidence: 99%